Household environmental characteristics influence the house dust metagenome - Isabella Gamez; Farnaz Fouladi; Antonio Gonzalez; James Ward; Ziyue Wang; Laura E. Beane Freeman; Alison Motsinger-Reif; Shyamal D. Peddada; Rob Knight; Mikyeong Lee; Stephanie J. London (Environmental Research, 2026)

High pesticide exposure events and subjective cognitive complaints among US farmers - Yaqun Yuan; Brenda L. Plassman; Shengfang Song; Zhehui Luo; Christine G. Parks; Jonathan N. Hofmann; Laura E. Beane Freeman; Dale P. Sandler; Honglei Chen (Environmental Research, 2026)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Carbaryl use and incident cancer in the Agricultural Health Study: an updated analysis - Patricia A. Erickson; Gabriella Andreotti; Richard V. Remigio; Mary H. Ward; Christine G. Parks; Dale P. Sandler; Paul S. Albert; Kathryn Hughes Barry; Jonathan N. Hofmann; Laura E. Beane Freeman (International Journal of Hygiene and Environmental Health, 2025)

Organochlorine pesticide use and mosaic loss of chromosome Y in a study of male farmers - Lauren M. Hurwitz; Vicky C. Chang; Laura E. Beane Freeman; Mitchell J. Machiela; Weiyin Zhou; Gabriella Andreotti; Christine G. Parks; Dale P. Sandler; Nathaniel Rothman; Sonja I. Berndt; Jonathan N. Hofmann; Stella Koutros (Environmental Research, 2025)

Occupational pesticide use and relative leukocyte telomere length in the biomarkers of exposure and effect in agriculture study - Patricia A. Erickson; Vicky C. Chang; Shisi He; Casey Dagnall; Kedest Teshome; Mitchell J. Machiela; Kathryn Hughes Barry; Edna F.R. Pereira; Shahinaz M. Gadalla; Christine G. Parks; Sonja I. Berndt; Laura E. Beane Freeman; et al. (Environmental Research, 2025)

Pesticide use and inflammatory bowel disease in licensed pesticide applicators and spouses in the Agricultural Health Study - Dazhe Chen; Christine G. Parks; Jonathan N. Hofmann; Laura E. Beane Freeman; Dale P. Sandler (Environmental Research, 2024)

Nitrate exposure from drinking water and dietary sources among Iowa farmers using private wells - Timothy G. Skalaban; Darrin A. Thompson; Jessica M. Madrigal; Benjamin C. Blount; Maria Morel Espinosa; Dana W. Kolpin; Nicole C. Deziel; Rena R. Jones; Laura Beane Freeman; Jonathan N. Hofmann; Mary H. Ward (Science of The Total Environment, 2024)

Occupational farm work activities influence workers’ indoor home microbiome - Kathryn R. Dalton; Mikyeong Lee; Ziyue Wang; Shanshan Zhao; Christine G. Parks; Laura E. Beane-Freeman; Alison A. Motsinger-Reif; Stephanie J. London (Environmental Research, 2024)

Joint associations between established genetic susceptibility loci, pesticide exposures, and risk of prostate cancer - Lauren M. Hurwitz; Laura E. Beane Freeman; Gabriella Andreotti; Jonathan N. Hofmann; Christine G. Parks; Dale P. Sandler; Jay H. Lubin; Jia Liu; Kristine Jones; Sonja I. Berndt; Stella Koutros (Environmental Research, 2023)

Exposure to pesticides and risk of Hodgkin lymphoma in an international consortium of agricultural cohorts (AGRICOH) - Joanne Kim; Maria E. Leon; Leah H. Schinasi; Isabelle Baldi; Pierre Lebailly; Laura E. Beane Freeman; Karl-Christian Nordby; Gilles Ferro; Alain Monnereau; Maartje Brouwer; Kristina Kjaerheim; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2023)
Purpose Some pesticides may increase the risk of certain lymphoid malignancies, but few studies have examined Hodgkin lymphoma (HL). In this exploratory study, we examined associations between agricultural use of 22 individual active ingredients and 13 chemical groups and HL incidence. Methods We used data from three agricultural cohorts participating in the AGRICOH consortium: the French Agriculture and Cancer Cohort (2005–2009), Cancer in the Norwegian Agricultural Population (1993–2011), and the US Agricultural Health Study (1993–2011). Lifetime pesticide use was estimated from crop-exposure matrices or self-report. Cohort-specific covariate-adjusted overall and age-specific (< 40 or ≥ 40 years) hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression and combined using random effects meta-analysis. Results Among 316 270 farmers (75% male) accumulating 3 574 815 person-years at risk, 91 incident cases of HL occurred. We did not observe statistically significant associations for any of the active ingredients or chemical groups studied. The highest risks of HL overall were observed for the pyrethroids deltamethrin (meta-HR = 1.86, 95% CI 0.76–4.52) and esfenvalerate (1.86, 0.78–4.43), and inverse associations of similar magnitude were observed for parathion and glyphosate. Risk of HL at ≥ 40 years of age was highest for ever-use of dicamba (2.04, 0.93–4.50) and lowest for glyphosate (0.46, 0.20–1.07). Conclusion We report the largest prospective investigation of these associations. Nonetheless, low statistical power, a mixture of histological subtypes and a lack of information on tumour EBV status complicate the interpretability of the results. Most HL cases occurred at older ages, thus we could not explore associations with adolescent or young adult HL. Furthermore, estimates may be attenuated due to non-differential exposure misclassification. Future work should aim to extend follow-up and refine both exposure and outcome classification.

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Pesticide use and risk of Hodgkin lymphoma: results from the North American Pooled Project (NAPP) - Lidija Latifovic; Laura E. Beane Freeman; John J. Spinelli; Manisha Pahwa; Linda Kachuri; Aaron Blair; Kenneth P. Cantor; Shelia Hoar Zahm; Dennis D. Weisenburger; John R. McLaughlin; James A. Dosman; Punam Pahwa; et al. (Cancer Causes & Control, 2020)
Purpose The purpose of this study was to investigate associations between pesticide exposures and risk of Hodgkin lymphoma (HL) using data from the North American Pooled Project (NAPP). Methods Three population-based studies conducted in Kansas, Nebraska, and six Canadian provinces (HL = 507, Controls = 3886) were pooled to estimate odds ratios and 95% confidence intervals for single (never/ever) and multiple (0, 1, 2–4, ≥ 5) pesticides used, duration (years) and, for select pesticides, frequency (days/year) using adjusted logistic regression models. An age-stratified analysis (≤ 40/ > 40 years) was conducted when numbers were sufficient. Results In an analysis of 26 individual pesticides, ever use of terbufos was significantly associated with HL (OR: 2.53, 95% CI 1.04–6.17). In age-stratified analyses, associations were stronger among those ≤ 40 years of age. No significant associations were noted among those > 40 years old; however, HL cases ≤ 40 were three times more likely to report ever using dimethoate (OR: 3.76 95% CI 1.02–33.84) and almost twice as likely to have ever used malathion (OR: 1.86 95% CI 1.00–3.47). Those ≤ 40 years of age reporting use of 5 + organophosphate insecticides had triple the odds of HL (OR: 3.00 95% CI 1.28–7.03). Longer duration of use of 2,4-D, ≥ 6 vs. 0 years, was associated with elevated odds of HL (OR: 2.59 95% CI 1.34–4.97). Conclusion In the NAPP, insecticide use may increase the risk of HL, but results are based on small numbers.

Cancer incidence in the Agricultural Health Study after 20 years of follow-up - Catherine C. Lerro; Stella Koutros; Gabriella Andreotti; Dale P. Sandler; Charles F. Lynch; Lydia M. Louis; Aaron Blair; Christine G. Parks; Srishti Shrestha; Jay H. Lubin; Paul S. Albert; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2019)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Pesticide use and fatal injury among farmers in the Agricultural Health Study - Jenna K. Waggoner; Paul K. Henneberger; Greg J. Kullman; David M. Umbach; Freya Kamel; Laura E. Beane Freeman; Michael C. R. Alavanja; Dale P. Sandler; Jane A. Hoppin (International Archives of Occupational and Environmental Health, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Cigarette smoking, alcohol intake, and thyroid cancer risk: a pooled analysis of five prospective studies in the United States - Cari M. Kitahara; Martha S. Linet; Laura E. Beane Freeman; David P. Check; Timothy R. Church; Yikyung Park; Mark P. Purdue; Catherine Schairer; Amy Berrington de González (Cancer Causes & Control, 2012)

Methyl bromide exposure and cancer risk in the Agricultural Health Study - Kathryn Hughes Barry; Stella Koutros; Jay H. Lubin; Joseph B. Coble; Francesco Barone-Adesi; Laura E. Beane Freeman; Dale P. Sandler; Jane A. Hoppin; Xiaomei Ma; Tongzhang Zheng; Michael C. R. Alavanja (Cancer Causes & Control, 2012)

Poultry and livestock exposure and cancer risk among farmers in the agricultural health study - Laura E. Beane Freeman; Anneclaire J. DeRoos; Stella Koutros; Aaron Blair; Mary H. Ward; Michael Alavanja; Jane A. Hoppin (Cancer Causes & Control, 2012)

Physical activity, diabetes, and thyroid cancer risk: a pooled analysis of five prospective studies - Cari M. Kitahara; Elizabeth A. Platz; Laura E. Beane Freeman; Amanda Black; Ann W. Hsing; Martha S. Linet; Yikyung Park; Catherine Schairer; Amy Berrington de González (Cancer Causes & Control, 2012)

Body mass index, agricultural pesticide use, and cancer incidence in the Agricultural Health Study cohort - Gabriella Andreotti; Lifang Hou; Laura E. Beane Freeman; Rajeev Mahajan; Stella Koutros; Joseph Coble; Jay Lubin; Aaron Blair; Jane A. Hoppin; Michael Alavanja (Cancer Causes & Control, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Occupational exposure to terbufos and the incidence of cancer in the Agricultural Health Study - Matthew R. Bonner; Brent A. Williams; Jennifer A. Rusiecki; Aaron Blair; Laura E. Beane Freeman; Jane A. Hoppin; Mustafa Dosemeci; Jay Lubin; Dale P. Sandler; Michael C. R. Alavanja (Cancer Causes & Control, 2010)

Endotoxin exposure and lung cancer risk: a systematic review and meta-analysis of the published literature on agriculture and cotton textile workers - Virissa Lenters; Ioannis Basinas; Laura Beane-Freeman; Paolo Boffetta; Harvey Checkoway; David Coggon; Lützen Portengen; Malcolm Sim; Inge M. Wouters; Dick Heederik; Roel Vermeulen (Cancer Causes & Control, 2010)